Chinese society: change, conflict and resistance (Abingdon, 2010)
"This bestselling introduction to Chinese society uses the themes of resistance and protest to explore the complexity of life in contemporary China. An interdisciplinary and international team of China scholars draw on perspectives from sociology, anthropology, psychology, history and political science and covers a broad range of issues. Topics covered include: * labour and environmental disputes * rural and ethnic conflict * migration * legal challenges * intellectual and religious dissidence * opposition to family planning. The newly revised, third edition adds two new chapters on gender and the family, and the reform of the Hukou system thus providing a comprehensive text for both undergraduates and specialists in the field, encouraging the reader to challenge conventional images of contemporary Chinese society."